Gadgets and English Vocabulary Acquisition of Rural Preschool Children in Malang - Robbithotul Rohmah, Ula; Indah, Rohmani Nur (STAIN Majene, 2023)
Gadgets are often considered to interfere with early childhood development, but gadget technology benefits children's language acquisition. This study aims to determine the English vocabulary acquisition of children aged four to six years from their habit of accessing entertainment through gadgets. The participants in this study were 53 children aged 4-6 years in a rural preschool in Malang. This research used a qualitative method with a descriptive explanation. Data collection techniques were conducted through class observation and interviews with teachers and parents. The results of this study showed that the subjects' foreign language proficiency in English was seen from the acquisition of vocabulary and understanding of the content they watched repeatedly. Second language mastery is also seen in the subject's ability to mention colors, simple verbs, nouns, and adjectives in English. The children acquired their foreign language of both expressive and receptive English vocabulary through their gadgets with the support of parental guidance. It implies that gadgets with controlled screen time and supervision can positively impact children’s foreign language acquisition.